In Vitro antileishmania activity of sesquiterpene-rich essential oils from Nectandra species - Lauriane Serpa Silva Bosquiroli; Ana Caroline dos Santos Ferreira; Katyuce Souza Farias; Eduarda Carneiro da Costa; Maria de Fátima Cepa Matos; Mônica Cristina Toffoli Kadri; Yasmin Silva Rizk; Flávio Macedo Alves; Renata Trentin Perdomo; Carlos Alexandre Carollo; Carla Cardozo Pinto de Arruda (Taylor & Francis Group, 2017)
Context: New antileishmanias are needed because of toxicity, high cost and resistance problems associated with available drugs. Nectandra (Lauraceae) produces several classes of compounds but its essential oil has not previously been reported to have antileishmania activity. Objective: We evaluated the cytotoxicity and antileishmania activity of essential oils from Nectandra amazonum Nees, N. gardneri Meisn., N. hihua (Ruiz & Pav.) Rohwer and N. megapotamica (Spreng.) Mez. Materials and methods: Nectandra oils were extracted from stem bark/leaves by hydrodistillation and compounds were identified by GC-MS. Oils were tested against Leishmania infantum and L. amazonensis intracellular amastigotes and nitric oxide production was evaluated. Cytotoxicity was achieved on NIH/3T3 and J774.A1 cells for the selectivity index (SI). Results and discussion: Nectandra gardneri was active against L. infantum and L. amazonensis (IC50 =  2.7 ± 1.3/2.1 ± 1.06 μg/mL) and contained 85.4% sesquiterpenes, of which 58.2% was intermediol. Besides low cytotoxicity (SI >11.3), N. gardneri induced a significant increase in NO production by L. infantum-infected macrophages. Nectandra hihua had the best activity on L. infantum amastigotes (IC50 =  0.2 ± 1.1 μg/mL). This oil was 89.0% sesquiterpenes, with 28.1% bicyclogermacrene. The two specimens of N. megapotamica had different activities on amastigotes. The one richer in sesquiterpenes (49.9%) was active against both species (IC50 =  12.5 ± 1.4/21.3 ± 1.2) and had phenylpropanoid E-asarone as the main compound (42.4%). Nectandra amazonum showed moderate activity on both the species (IC50 =  31.9 ± 2.0/22.1 ± 1.3 μg/mL) and low selectivity (0.9 < SI >2.6), probably due to the major presence of β-caryophyllene (28.5%). Conclusions: Our data identify compounds that can now be isolated and used for the development of new antileishmanias.